Visual Literacy in Elemntary English Learning: Using Picture Book to Foster Language Development - Tiarnita Maria Sarjani Siregar; Dhea Ananda Br Barus; Mutiah Mutadayyinah Marbun; Sasri Agustina Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to examine the use of picture books as a visual literacy medium in teaching English at the elementary school level, particularly in the context of English as a Foreign Language (EFL). This research employed a qualitative descriptive literature review by analyzing relevant national and international journal articles published within the last five years. The findings indicate that the integration of visual and verbal elements in picture books contributes significantly to students’ language development, especially in vocabulary acquisition, reading comprehension, and meaning construction. From an affective perspective, the use of picture books enhances students’ motivation, learning interest, classroom participation, and reduces language learning anxiety. The effectiveness of visual media is theoretically supported by Dual Coding Theory, which explains that information processed through both verbal and visual channels strengthens memory retention and comprehension. However, several challenges remain, including the selection of appropriate picture books and teachers’ limited competence in visual literacy. Therefore, systematic instructional planning and professional development for teachers are essential to optimize the use of picture books in EFL classrooms at the elementary level.